2014
DOI: 10.1177/0969733014557119
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s experiences of their free will in nursing homes

Abstract: Results may benefit ethical education and promote the ethical quality of older people's care practice and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 37 publications
2
69
2
2
Order By: Relevance
“…Legal regulations demand the protection of residents in nursing homes, but “such laws encourage institutional personnel to adopt paternalizing practices that impose protection at the cost of freedom” (McClean, , p. 111). Locked doors and coded elevators can also be seen as obstacles to free will (Tuominen et al, ). As restricted mobility is commonly linked to those who are a security threat to society (Moran, ), the feeling of being incarcerated is specifically connected to limiting an individual's mobility.…”
Section: “Locked Up”mentioning
confidence: 99%
“…Legal regulations demand the protection of residents in nursing homes, but “such laws encourage institutional personnel to adopt paternalizing practices that impose protection at the cost of freedom” (McClean, , p. 111). Locked doors and coded elevators can also be seen as obstacles to free will (Tuominen et al, ). As restricted mobility is commonly linked to those who are a security threat to society (Moran, ), the feeling of being incarcerated is specifically connected to limiting an individual's mobility.…”
Section: “Locked Up”mentioning
confidence: 99%
“…Some older people in nursing homes are not as lucky. For example, one study showed older people in a nursing home felt they did not possess complete free will . Although the residents had choice in many aspects of their lives, such as when to go to bed, this was not true of other activities; for example, when or how they get showered and go to the toilet.…”
Section: Taken From Ransom S (2000) This Table Denotes the Findings mentioning
confidence: 99%
“…For example, one study showed older people in a nursing home felt they did not possess complete free will. 10 Although the residents had choice in many aspects of their lives, such as when to go to bed, this was not true of other activities; for example, when or how they get showered and go to the toilet. The same study identified several barriers to nurses being able to offer a greater range of choice, including perceptions of work from an organizational perspective such as the need to provide meals at specific times.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These disorders often restrict their activities and ultimately have an inappropriate effect on their daily life (3,5). Maintaining the health of the elderly requires the attention to their health throughout their lifespan, support of lifestyle changes that arise via a variety of occupational, cultural, social, and rehabilitation factors, and an appro-priate environment (6,7). In recent years, the provision of facilities including charities and pensions centers, etc.…”
Section: Introductionmentioning
confidence: 99%